POTENSI KOMBINASI RUXOLITINIB DENGAN INHIBITOR PI3K/mTOR BEZ235 TERENKAPSULASI NANOKRISTAL KALSIUM KARBONAT PADA PENDERITA POLISITEMIA VERA - Ariawan, I Wayan Tegar Raharja; Divasta, I G Mahapraja; Maharani, Putu Ayu Pradnya Gita (Essence of Scientific Medical Journal; Vol 21 No 1 (2023): Volume 21 No. 1 (Januari - Juni 2023) Essential: Essence of Scientific Medical Journal, 2023)
ABSTRACT Introduction: Polycythemia vera (PV) is a condition in which janus kinase 2 (JAK2) in hematopoietic cells experiences hyperactivation resulting in phosphorylation of signal transducer and activator of transcription 5 (STAT5) in the absence of a ligand binding to the receptor. This condition causes excessive production of blood cells, especially erythrocytes. The hyperactivation was caused by a V617F mutation in JAK2 which disrupted the interaction of the jak homology 1 (JH1) and jak homology 2 (JH2) domains. Polycythemia vera can cause complications such as thrombosis, hypertension, and splenomegaly. If prolonged, polycythemia vera can develop into myelofibrosis. In addition, JAK2 hyperactivation also causes an increase in phosphatidylinositol 3-kinase (PI3K) activity which also leads to STAT5 phosphorylation.   Discussion: Currently, the most widely used therapy for polycythemia vera is ruxolitinib. However, ruxolitinib has drawbacks, namely it cannot completely inhibit STAT5 phosphorylation and can increase the risk of reactivation of herpes zoster which can be inhibited by PI3K inhibitors. Therefore, an alternative therapy is needed, namely a combination of ruxolitinib with PI3K inhibitors, one of which is BEZ235. BEZ235 is a PI3K/Mammalian Target of Rapamycin (mTOR) inhibitor which has the potential to be combined with ruxolitinib. BEZ235 was able to prevent incomplete inhibition of STAT5 phosphorylation. However, BEZ235 has low bioavailability, so encapsulation efforts need to be made, one of which is by using CaCO3 nanocrystals. Overall, the combination of ruxolitinib with BEZ235 showed better results than the administration of the drug without the combination.   Conclusion: Therefore, the authors want to examine more deeply the potential of BEZ235 encapsulated CaCO3 nanocrystals combined with ruxolitinib for its potential as a therapy for polycythemia vera.